2019
DOI: 10.1080/00036846.2019.1638499
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peer observation on consumption choices: evidence from a lab-in-field experiment

Abstract: We investigate the impact of peer observation on consumption decisions using a lab-in-field experiment. Respondents make consumption decisions either alone or under peer observation. We find evidence for peer effects. We are able to study these further by looking into the mechanism and performing detailed heterogeneity analysis. Concerning the mechanisms, we find evidence for an information channel. Further, we show that the consumption choice is influenced by how many people made the same decision previously,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…An example is provided by people belonging to a reference group of people (colleagues, members of the family, friends...) whose consumption of the good can be considered a reference for the consumer who does not want to behave too differently from them. A classic example is the consumption of tobacco or alcohol among adolescents (Varela & Pritchard 2011, Grohmann & Sakha 2019. Even if some of them may not appreciate a high level of consumption of these products, the high consumption of peers may influence their behavior because they do not want to feel excluded by the group.…”
Section: The Model With Reference Quantitymentioning
confidence: 99%
“…An example is provided by people belonging to a reference group of people (colleagues, members of the family, friends...) whose consumption of the good can be considered a reference for the consumer who does not want to behave too differently from them. A classic example is the consumption of tobacco or alcohol among adolescents (Varela & Pritchard 2011, Grohmann & Sakha 2019. Even if some of them may not appreciate a high level of consumption of these products, the high consumption of peers may influence their behavior because they do not want to feel excluded by the group.…”
Section: The Model With Reference Quantitymentioning
confidence: 99%
“…Empirics also provides evidence of peer effects on selfcontrol as a concept related to time preferences. For example, Grohmann and Sakha (2019) studied the effects of peer observation on a choice of temptation goods vs. money on a sample of individuals from rural villages in Thailand, and found evidence of peer effects. They further demonstrated that the consumption choice was influenced by the number of people who made the same decision previously, but not by the identity of those people.…”
Section: Shaping Of Intertemporal Decisionsmentioning
confidence: 99%
“…Few research looks into the mechanisms behind peer effects and what leads to conformity. Grohmann and Sakha (2019) provides the first insight into mechanisms by conducting a lab-in-field experiment linked to a very detailed household survey. The identification problems found in studies on peer effects are addressed based on the experimental design and the use of a large number of control variables.…”
Section: Review Of Empirical Resultsmentioning
confidence: 99%
“…Cai et al (2009) applies an experimental design in the restaurant context to reveal that information content of other's choices affect the demand for dishes. Grohmann and Sakha (2019) applies a lab-in-field experiment to find evidence o both information and psychological channel underlying peer effects.…”
Section: Mechanisms Underlying Social Effectsmentioning
confidence: 99%
See 1 more Smart Citation